Isolation and Characterization of Antioxidant Peptides from Dairy Cow (Bos taurus) Placenta and Their Antioxidant Activities - Xinyu Tian; Zeru Zhang; Yuquan Zhao; Anguo Tang; Zhi Zeng; Weijian Zheng; Hanwen Zhang; Yuxin Luo; Wei Lu; Lei Fan; Liuhong Shen (MDPI AG, 2024)
Our preliminary study identified dairy cow placenta extract (CPE) as a mixture of peptides with potent antioxidant activity both in vivo and in vitro. However, the specific antioxidant peptides (AOPs) responsible for this activity were not yet identified. In the current study, we employed virtual screening and chromatography techniques to isolate two peptides, ANNGKQWAEVF (CP1) and QPGLPGPAG (CP2), from CPE. These peptides were found to be less stable under extreme conditions such as high temperature, strong acid, strong alkali, and simulated digestive conditions. Nevertheless, under normal physiological conditions, both CP1 and CP2 exhibited significant antioxidant properties, including free-radical scavenging, metal chelating, and the inhibition of lipid peroxidation. They also up-regulated the activities of intracellular antioxidant enzymes in response to hydrogen-peroxide-induced oxidative stress, resulting in reduced MDA levels, a decreased expression of the Keap1 gene and protein, and increased levels of the Nrf2 and HO-1 genes and proteins. Furthermore, CP1 demonstrated superior antioxidant activity compared to CP2. These findings suggest that CP1 and CP2 hold potential for mitigating oxidative stress in vitro and highlight the efficacy of virtual screening as a method for isolating AOPs within CPE.